Effects of feeding whole linseed on ruminal fatty acid composition and microbial population in goats - Abuelfatah, Kamaleldin; Abu Bakar @ Zakaria, Md Zuki; Goh, Yong Meng; Sazili, Awis Qurni; Abu Bakar, Abdelrahim (Elsevier, 2016)
The objective of the present study was to evaluate the effect of feeding different levels of whole linseed, as a source of n-3 polyunsaturated fatty acids (PUFA), on ruminal fatty acid composition and microbial population in the goat. Twenty-four crossbred Boer goats were assigned to 3 dietary treatments: L0 (control), L10 and L20 containing 0, 10%, or 20% whole linseed, respectively. The ruminal pH and concentration of total volatile fatty acids (VFA) were not affected by dietary treatments. The feeding of L10 and L20 diets produced higher (P < 0.05) molar proportions of acetate and lower (P < 0.05) molar proportions of butyrate and valerate than the L0 diet. Molar proportions of myristic acid (C14:0) and palmitic acid (C16:0) were lower (P < 0.05) in the rumen of goats offered L10 and L20 diets than the control diet. However, stearic acid (C18:0), vaccenic acid (C18:1 trans-11), conjugated linoleic acid (CLA, C18:2 trans-10, cis-12) and α-lenolenic acid (C18:3 n-3) were higher (P < 0.05) in the rumen of goats fed L10 and L20 than L0. Both inclusion levels of linseed in the diet (L10 and L20) reduced the ruminal total bacteria, methanogens, and protozoa compared with L0 (P < 0.05). The effect of the dietary treatments on cellulolytic bacteria, varied between the individual species. Both inclusion levels of linseed resulted in a significant decrease (P < 0.05) in the population of Fibrobacter succinogenes, and Rumunococus flavefaciens compared with L0, with no significant difference between the groups fed linseed diets. The population of Rumunococus albus was not affected by the different dietary treatments. It was concluded that inclusion of whole linseed in the diet of goats could increase the concentration of PUFA in the rumen, and decrease the population of F. succinogenes, R. flavefaciens, methanogens and protozoa in rumen liquid of goats.